Alphabet Soup: Consumer’s Perceptions of Social Enterprise Terminology in Marketing Communications - Reavey, Brooke; Guarise, Rafaela (Journal of Marketing Development and Competitiveness, 2020)
Academically, the definition of fair trade, ethical buying and sustainable consumption are distinct concepts. But little research has explored how consumers perceive these concepts. Can they tell the difference between them? Should marketers choose one term over the other? In an effort to investigate this marketing communications issue, we ran an exploratory study among 197 American consumers. We discover through the use of content analysis and correspondence analysis that consumers do not view these terms as separate constructs. Viewed from a spreading activation theory lens, we discuss the practical and academic implications of these findings.